Assessment of the structures at risk during wrist arthroscopy: a cadaveric study and systematic review. (October 2016) - Shyamalan, G.; Jordan, R. W.; Kimani, P. K.; Liverneaux, P. A.; Mathoulin, C.
We assessed the proximity of neurological structures to arthroscopic portals in a cadaveric study and through a systematic review. Arthroscopy was performed on ten cadaveric wrists. Subsequently the specimens were dissected to isolate the superficial branch of the radial nerve, the dorsal branch of the ulnar nerve, the posterior interosseous nerve and the extensor tendons. We measured the distances from the nerves to common portals. For the systematic review Pubmed and EMBASE were searched on the 31 May 2014 for cadaveric studies reporting the proximity of neurological structures to any arthroscopic wrist portal. In the cadaveric study, partial injuries were seen to six extensor tendons and one posterior interosseous nerve; it was assumed this was due to creation of the portals. Seven published studies were included in the systematic review. The dorsal sensory branch of the ulnar nerve was found to be at risk by performing the 6 Ulnar, 6 Radial and ulnar midcarpal portals, the sensory branch of the radial nerve by the 1–2 and 3–4 portals and the posterior interosseous nerve by the 3–4 and 4–5 portals. Level of evidence: V